PERAN DINAS PERIKANAN DALAM PEMBERDAYAAN MASYARAKAT PADA SENTRA PENGOLAHAN IKAN PATIN PASCA PANEN DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR TAHUN 2018-2019 - Rarito S, Muhammad Aldi; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Abundant yields and high competition make it difficult for farmers to find a market that is willing to accept a fair price. It takes a wider market share and raw fish processing techniques to make it durable for consumption. One of the efforts currently being made by farmers is to diversify the product into smoked fish and fillets. However, to be able to do this, of course, requires a large amount of capital as well as adequate support and infrastructure, which is difficult for farmers to do. The purpose of this study was to see the role of the Fisheries Service and the obstacles faced in community empowerment at post-harvest catfish processing centers in Koto Mesjid Village, XIII Koto Kampar District, Kampar Regency.            This research use desciptive qualitative approach. Then the data collection techniques used were interviews, observation and documentation. While the data analysis technique is carried out by collecting information through interviews, data reduction and data presentation.            Based on the results of the research, it was found that the role of the Fisheries Service in community empowerment at post-harvest catfish processing centers in Koto Mesjid Village was in the form of facilities and infrastructure assistance as well as training and coaching programs. Meanwhile, the obstacles faced in carrying out activities were intrinsic constraints which included low public awareness and budget constraints. Meanwhile, extrinsic controls include the price of raw materials, the cost of production which is increasing over time, product durability related to mileage, product standards and licensing. Keywords: Role, Community Empowerment and Post Harvest.